THE USE OF MCM-48-nCaO AS CATALYST IN ESTERIFICATION REACTION OF NYAMPLUNG SEED OIL (Calophyllum inophyllum L.) - La Kolo; Firdaus Firdaus; Paulina Taba (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2015)
A study on the use of MCM-48-nCaO as a catalyst in the esterification reaction of nyamplung seed oil (Calophyllum inophyllum L.) has been carried out. The characterization results of XRF, XRD and FTIR showed the success in the synthesis of heterogeneous catalysts, MCM-48- nCaO, using a grinding-impregnation method. Through esterification reaction using the catalysts, FFA content in the seed oil of nyamplung reduced from 28 to 1.7%.